1994
DOI: 10.1099/0022-1317-75-2-405
|View full text |Cite
|
Sign up to set email alerts
|

Sequences of wild Puumala virus genes show a correlation of genetic variation with geographic origin of the strains

Abstract: An experimental scheme was developed for direct sequence analysis of Puumala virus-containing specimens from wild rodents (Clethrionomys glareolus). Total RNA isolated from rodent lung tissues was reversetranscribed in the presence of a universal 11 nucleotide primer complementary to all three viral RNA segments followed by amplification in a PCR with gene-specific primers. A full-length PCR product of approximately 1800 bp from the S segment encoding the viral nucleoprotein and a product of approximately 900 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
57
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 13 publications
9
57
0
Order By: Relevance
“…16 These data were also consistent with the geographic-specific lineages shown previously for rodent-borne hantaviruses, including HTNV in Apodemus agrarius , 26 Soochong virus in Apodemus peninsulae , 27 Puumala virus in Myodes glareolus , 28,29 Muju virus in Myodes regulus , 30 and Tula virus in Microtus arvalis . 31 Overall, these data were suggestive of long-standing associations between hantaviruses and their reservoir rodent and soricid hosts, but the basis for these relationships through evolutionary time is unclear.…”
supporting
confidence: 88%
“…16 These data were also consistent with the geographic-specific lineages shown previously for rodent-borne hantaviruses, including HTNV in Apodemus agrarius , 26 Soochong virus in Apodemus peninsulae , 27 Puumala virus in Myodes glareolus , 28,29 Muju virus in Myodes regulus , 30 and Tula virus in Microtus arvalis . 31 Overall, these data were suggestive of long-standing associations between hantaviruses and their reservoir rodent and soricid hosts, but the basis for these relationships through evolutionary time is unclear.…”
supporting
confidence: 88%
“…According to a theory proposed by Plyusnin et al [30,31], the extent of hantavirus diversity is proportional to the geographic distance between the areas of their circulation. However, while the microgeographical relationships among hantaviruses might be linearly proportional, the macrogeographical relationships are likely to be more complex.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of hantaviruses in northern Europe identified four distinct genetic lineages of PUUV: Finnish (FIN), North Scandinavian (N-SCA), South Scandinavian (S-SCA) and Danish (DAN) (Plyusnin et al, 1994(Plyusnin et al, , 1995Hörling et al, 1996;Lundkvist et al, 1998;Asikainen et al, 2000;Sironen et al, 2002;Johansson et al, 2008). The FIN lineage was recovered from bank voles trapped in southcentral Finland and Russian Karelia, the DAN lineage originated from the Danish island of Fyn, and the lineages N-SCA and S-SCA were identified in bank vole populations that located to the north and south of the Scandinavian bank vole population border, respectively.…”
Section: Introductionmentioning
confidence: 99%